KAJIAN KEKOHESIFAN DAN KEKOHERENSIAN TAJUK RENCANA PADA MEDIA DARING TRIBUN JAMBI - Mila Martina; Akhyaruddin Akhyaruddin; Priyanto Priyanto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the forms of cohesion and coherence in editorials in the June to August 2023 edition of Tribun Jambi online media. The type of research used is descriptive qualitative with a content analysis approach. Data in the form of cohesion and coherence forms and data sources for editorials in the June to August 2023 edition of Tribunjambi.com. Data collection techniques using document techniques, and listening which are then classified in the form of codes and data tables. The data validity test is source triangulation by using various relevant sources to check and compare. Data analysis techniques include: 1) data identification, 2) data classification, 3) data analysis, 4) data presentation, and 5) conclusion drawing. The results showed that the editorial plans in the online media Tribun Jambi used grammatical cohesion, lexical cohesion, and coherence with the amount of data found, namely 388 data. In the aspect of grammatical cohesion, 175 references, 2 substitutions, and 64 conjunctions were found. Furthermore, in lexical cohesion, 4 synonyms, 2 antonyms, 5 hyponyms, 71 repetitions, 7 collocations, and 3 equivalences were found. While the forms of coherence are 16 cause-effect relationships, 4 means-result relationships, 24 means-purpose relationships, 3 paraphrastic relationships, 7 identification relationships, and 1 generic-specific relationship.